Rhabdomyosarcoma of the biliary tract in a child: a case report - Ran, Tang; Gong, Chen; Rui, Dong; Shan, Zheng (Frontiers in Pediatrics, 2024)
Pediatric rhabdomyosarcoma of the biliary tract (BRMS) is extremely rare. Here, we present a case of a 2-year-old child who was initially misdiagnosed with choledocholithiasis upon admission. The diagnosis was later confirmed as BRMS through endoscopic retrograde cholangiopancreatography (ERCP). The patient was cured through surgery followed by chemotherapy. Due to the lack of specific early symptoms and the challenges in imaging differentiation, particularly in pediatric patients, clinical awareness of this condition needs to be heightened. Our findings indicate that ERCP is currently the optimal diagnostic tool for this disease, and a combination of surgery and chemotherapy can yield better therapeutic outcomes.